Digital Marketing Strategy for Medical Supplier Company in Covid-19 Pandemic Era - Mona, Nailul; Audini, Yassmine (Future Science / FSH-PH Publications, 2023)
In the covid-19 global pandemic era, many countries apply restriction for many offline activities in order to prevent virus spread. This affected many business and force them to go online. Every business have to adapt and adopt technology within this pandemic situation. One of the business whose product demand are increasing, is a medical supplier company. But this increase not only in the matter of demand, but also competitor and product variation. Existing company should run digital transformation to secure and expand their position on the market. This paper explain digital marketing communication strategies which conducted by medical supplier company in covid-19 pandemic era. The company make use of some platform for the initial digital marketing strategy, such as social media activation, company website, and e-commerce. Result shows that digital marketing plays important role for product sales escalation. Company can promote their business and establish customer relationship through various digital channel. However, e-commerce strategy seems more challenging for medical supplier company. This paper could help other business to determine their suitable digital marketing communication strategy.